1995
DOI: 10.1111/j.1365-2141.1995.tb08410.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometry analysis of dual red blood cell populations after bone marrow transplantation

Abstract: Flow cytometry represents an alternative method to agglutination assays for the accurate quantification of mixed field populations of erythrocytes observed after bone marrow transplantation. Murine monoclonal antibodies directed against the blood group ABH antigens were selected and processed in order to prepare ready-to-use fluorescent reagents. Anti-A (NaM8 7-1F6; IgG3), anti-B (NaM9-2E11: IgG3) and anti-H (NaM19-7Ell; IgM) were purified, labelled with fluorescein isothiocyanate, and used in a direct flow cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Continuing quantitation of the differences can give early warning of loss of the graft or confirmation of a stable chimera (Arnold et al, 1986;Blanchard et al, 1995;Lazarus et al, 1992). Continuing quantitation of the differences can give early warning of loss of the graft or confirmation of a stable chimera (Arnold et al, 1986;Blanchard et al, 1995;Lazarus et al, 1992).…”
Section: F Cell Cycle Studiesmentioning
confidence: 99%
“…Continuing quantitation of the differences can give early warning of loss of the graft or confirmation of a stable chimera (Arnold et al, 1986;Blanchard et al, 1995;Lazarus et al, 1992). Continuing quantitation of the differences can give early warning of loss of the graft or confirmation of a stable chimera (Arnold et al, 1986;Blanchard et al, 1995;Lazarus et al, 1992).…”
Section: F Cell Cycle Studiesmentioning
confidence: 99%
“…This method relies on its ability to discriminate transfused from endogenously produced RBC populations. Flow cytometry has been used to detect fetomaternal hemorrhage (4, 5), determine RBC phenotype following bone marrow transplant (6), measure RCV (7-9), detect illicit blood transfusions in athletes (10), and determine RBC survival (11, 12). Recently, our group has for the first time demonstrated that RCV can be accurately determined in adult humans and sheep using multiple distinct populations of biotin–labeled RBCs (BioRBCs) enumerated by flow cytometry (8, 13).…”
Section: Introductionmentioning
confidence: 99%
“…Use nonagglutinating (IgG) antibodies Chemically convert agglutinating IgM pentamers into nonagglutinating IgM monomers, e.g., using dithiothreitol [48,57] or 2-mercaptoethanol Purify IgG fractions of sera on Protein G [49] Dilute antisera past point of agglutination Avoid use of potentiators Chemically fix the RBCs prior to incubation with anti-A, -B, -M, or -N, e.g., with dimethylsuberimidate [74], formaldehyde [47,75], or glutaraldehyde [13,21,44,49] To avoid agglutination caused by secondary antibody:…”
Section: Selection Of Direct or Indirect Labeling Methods For Each Blomentioning
confidence: 99%
“…The analysis of mixed RBC populations occurring as a result of hematopoietic chimerism in twins [42][43][44][45][46] and in bone marrow transplant recipients [47][48][49][50][51][52] is easily performed by flow cytometry. This technique has also been used in studies of individuals with blood group mosaicism [26,[53][54][55].…”
Section: Chimerism and Mosaicismmentioning
confidence: 99%
See 1 more Smart Citation